2018
DOI: 10.1111/php.12993
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Inductions in Excited State Reactions: Photodimerization of Alkyl 2‐Naphthoates as a Model

Abstract: Enantioselectivity in organic transformations continues to be a topic major interest in organic photochemistry. In the last decade, synergistic combination of photocatalysis and organocatalysis has emerged as a powerful strategy to gain enantioselectivity in photochemical reactions, and remarkable achievements have been obtained. In this strategy, the asymmetric induction is provided in ground state. In contrast, in the conventional enantioselective photochemistry, the chiral induction is controlled in electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
(132 reference statements)
0
1
0
Order By: Relevance
“…Photocyclodimerizations of AC, 2, 6-anthracenedicarboxylate (ADC) ,, and 3-methoxyl-2-naphthoate (NA), (Figure ) were chosen to examine the performance of chiral photocatalysts. The UV–vis and circular dichroism spectral titration demonstrated that CD 1 – CD 5 could form 1:1 and 1:2 host–guest complexes with AC with good binding affinities (Figures S6–S20, Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Photocyclodimerizations of AC, 2, 6-anthracenedicarboxylate (ADC) ,, and 3-methoxyl-2-naphthoate (NA), (Figure ) were chosen to examine the performance of chiral photocatalysts. The UV–vis and circular dichroism spectral titration demonstrated that CD 1 – CD 5 could form 1:1 and 1:2 host–guest complexes with AC with good binding affinities (Figures S6–S20, Table S1).…”
Section: Resultsmentioning
confidence: 99%